1985
DOI: 10.1111/j.1532-5415.1985.tb01774.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Burden in Families Caring for a Relative With a Dementing Illness

Abstract: The purpose of this study was to investigate the efficacy of a specifically designed group support program for relatives of patients with Alzheimer's disease and related disorders. The group program included educational/supportive activities and used basic principles of the cognitive-behavioral approach. Twenty-two subjects participated in an eight-session program. Eighteen control subjects received no treatment. Measures of family burden, levels of depression, and knowledge of dementia were obtained. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 13 publications
5
46
2
Order By: Relevance
“…This might be due to the fact that more highly educated caregivers have better social and financial support and, therefore, are more able to adapt to the stress. The study of Kahan et al [29] also showed that knowledge about dementia is an important factor for decreasing the caregivers' burden. Therefore, caregivers with lower educational levels should have more support.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the fact that more highly educated caregivers have better social and financial support and, therefore, are more able to adapt to the stress. The study of Kahan et al [29] also showed that knowledge about dementia is an important factor for decreasing the caregivers' burden. Therefore, caregivers with lower educational levels should have more support.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the fact that more highly educated caregivers have more realistic expectations about the course of the disease as well as better social and financial support and, therefore, can adapt better to the stress and changing care needs of the person with AD. Also, knowledge about dementia and its management is an important factor for decreasing caregiver burden [31] . Therefore, caregivers with lower educational levels should be targeted to receive closer monitoring and support programs by governmental agencies and nongovernmental organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mental state and language were closely related to strain and these cognitive hnpairments were related to more emotional than practical aspects of caregiver strain. Some carers expressed a need for stroke carer support groups where they would be able to taUc to other people in the same situation: Support groups have shown to provide information and to promote interaction with others facmg the same situation (Barnes, 1981;Bishop et al, 1986;Kanan and Kempt, 1985;WUson, 1985) and they thrive on individuals sharing their personal experiences (WUson, 1985).…”
Section: Emotional Interventionmentioning
confidence: 99%